Exploring therapeutic mechanism of Fuzhenghefuzhiyang Formula in psoriasis: inflammation and metabolism regulation - Tang, Bin; Zhang, Chen; Yang, Yujie; Zhong, Haixin; Yang, Kexin; Deng, Hao; Yu, Jingjie; Chen, Yonggen; Deng, Xiangliang; Lu, Chuanjian; Chen, Haiming (Frontiers in Immunology, 2025)
BackgroundPsoriasis is a long-term, immune-mediated inflammatory disorder of the skin, affecting about 2-3% of the global population with rising prevalence rates. Clinical practice has demonstrated that Fuzhenghefuzhiyang formula (FZHFZY), a topical medication applied Chinese herbal formula developed by Prof. Lu Chuanjian, exhibits significant efficacy in alleviating psoriasis symptoms. Nevertheless, its mechanism of anti-psoriasis remains unclear.PurposeThe purpose of this study is to decode the molecular mechanisms by which FZHFZY produces its therapeutic effects on psoriasis using an integrated multi-omics approach.MethodsEmploying both cell-based and animal studies, we systematically elucidate the pharmacodynamic substance basis and biological pathways underlying its anti-psoriasis effects by integrating network pharmacology to predict the active ingredient-target network, metabolomics to analyze endogenous metabolite changes, and transcriptome sequencing to dissect gene expression regulation.ResultsFZHFZY effectively alleviated symptoms of skin thickening, erythema, and scaling in psoriatic model mice. Network pharmacology predicted that its therapeutic effect might be related to target pathways associated with inflammation, metabolism, proliferation, pyroptosis. RNA sequencing analysis of skin lesion tissues revealed that FZHFZY modulated the inflammation-related NOD-like receptor (NLR) and IL-17 signaling pathways. Further validation by RT-PCR showed that FZHFZY markedly downregulated the mRNA levels of IL-17 and NLRP3. Metabolomics analysis of the lesion tissues identified 169 differential metabolites, and FZHFZY was found to regulate the catabolism of carbohydrates, purines, and most amino acids. Cross-analysis of the two omics approaches indicated that purine metabolism and ether lipid metabolism were associated with key genes in the NLR signaling pathway identified by MCODE analysis.ConclusionsThis study revealed that FZHFZY can effectively improve lesion conditions in a psoriasis-like mouse model, and its mechanism of action may be related to the association between purine metabolism, lipid metabolism, and key genes in the NLR signaling pathway.